Pattern glare: the effects of contrast and color - Monger, Laura J.; Wilkins, Arnold J.; Allen, Peter M. (Frontiers in Psychology, 2015)
Aim: To test a theory of visual stress by investigating the inter-relationships between (1) the threshold contrast/saturation at which individuals first report discomfort when viewing colored gratings of progressively increasing contrast and decreasing saturation; (2) the choice of a colored overlay for reading; (3) any increase in reading speed when the overlay is used. Method: Ninety-five young adults, with normal color vision, reported illusions from square-wave gratings (Pattern Glare Test), chose any colored overlays that improved clarity (Intuitive Color Overlays) and read aloud randomly ordered common words (Wilkins Rate of Reading Test). This was followed by an automated choice of tints for text using various screen colors on a tablet, and a test of discomfort from patterns of progressively increasing contrast and decreasing saturation, using software developed for this study. All participants wore their optimal refractive correction throughout the procedure. Results: Fifty-eight participants chose a colored overlay and reported that it made text easier and more comfortable to read. On average, these individuals had a greater improvement in reading speed with their overlays (p = 0.003), a lower contrast threshold at which discomfort from achromatic gratings was first reported (p = 0.015), and a tendency to report more pattern glare (p = 0.052), compared to the other participants. Participants who chose both a most and least preferred tint for text using the automated procedure reported discomfort from colored gratings at a significantly higher contrast with their most preferred color compared to their least preferred color (p = 0.003). The choice of a colored tint was moderately consistent across tests. The most and least preferred colors tended to be complementary. Conclusion: Colored tints that improved reading speed reduced pattern glare both in terms of the illusion susceptibility and in terms of discomfort contrast threshold, supporting a theory of visual stress. An automated test that incorporates colored gratings and a choice of most and least preferred color might better identify individuals whose reading speed improves with colored overlays.